Symbolic artefacts in the Late Palaeolithic andthe early Mesolithic in Northern and Central Europe - Płonka, Tomasz; Kowalski, Krzysztof (Uniwersytet Wrocławski. Instytut Archeologii, 2017)
The symbolic culture at the end of the Palaeolithic and the beginning of theMesolithic is still poorly investigated. In our study, we looked for new perspectives onthe execution of symbolic objects and their manner-of-use. In Northern and CentralEurope Late Palaeolithic societies one finds carefully crafted bone and antler artefactscovered with painstakingly engraved ornaments, and also, figurines of animals made ofamber. These objects were not used as tools, were held onto for many years, and apparentlyplayed a central role in the social and religious life of the forager groups. A symbolmore significant than others appears to be the pattern of densely engraved zigzag lines.Its literal meaning is no longer available to us at present, nevertheless, it is likely to berelated to the aquatic element, the reflection of the growing role of the aquatic environmentin everyday life and in the symbolic culture. The wide distribution of densely engravedzigzag motif noted across Northern Europe suggests a free flow of information,ideas and beliefs within an open relationship network connecting different groups. In theearly Mesolithic finds decorated with densely engraved zigzag lines concentrate in tworegions: in what today is Denmark, and in central and south-western Finland, with somerare finds recorded in the British Isles and in the eastern Baltic region. Simple anthropomorphicmotifs in the stroke style are known mostly from the islands of Denmark. Thisgeographically confined distribution of this distinctive style is related presumably to theemergence of socio-cultural borders which separated societies with different traditions,organization and culture system.
Keywords: Late Palaeolithic; early Mesolithic; symbolic culture; engraved ornaments; zoo- and anthropomorphic representations